2014
DOI: 10.1038/srep04079
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanofiber aerogels for emergent cleanup of oil spillage and chemical leakage under harsh conditions

Abstract: To address oil spillage and chemical leakage accidents, the development of efficient sorbent materials is of global importance for environment and water source protection. Here we report on a new type of carbon nanofiber (CNF) aerogels as efficient sorbents for oil uptake with high sorption capacity and excellent recyclability. Importantly, the oil uptake ability of the CNF aerogels can be maintained over a wide temperature range, from liquid nitrogen temperature up to ca. 400°C, making them suitable for oil c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
107
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(109 citation statements)
references
References 53 publications
(67 reference statements)
2
107
0
Order By: Relevance
“…Within the sponge, numerous CNTs are self-assembled (overlapping on each other with some degree of intertwining) into a porous isotropic network, as characterized by scanning electron microscopy (SEM) (Figure 2 b). [ 31,[33][34][35]46,[65][66][67] The interconnected CNT network also renders the macroscopic sponge a good electrical conductivity (1.6 S cm −1 ). Here, the scaffold-like 3D framework is made from 1D cylindrical nanotube skeletons, resulting in a highly open-porous structure, as illustrated in Figure 2 c. In comparison, GO aerogels contain micrometerscale cells enclosed by 2D GO sheets, an intermediate structure between the open-pores and close-cells.…”
Section: Direct Growth Of Cnt Sponges By Floating Catalyst Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the sponge, numerous CNTs are self-assembled (overlapping on each other with some degree of intertwining) into a porous isotropic network, as characterized by scanning electron microscopy (SEM) (Figure 2 b). [ 31,[33][34][35]46,[65][66][67] The interconnected CNT network also renders the macroscopic sponge a good electrical conductivity (1.6 S cm −1 ). Here, the scaffold-like 3D framework is made from 1D cylindrical nanotube skeletons, resulting in a highly open-porous structure, as illustrated in Figure 2 c. In comparison, GO aerogels contain micrometerscale cells enclosed by 2D GO sheets, an intermediate structure between the open-pores and close-cells.…”
Section: Direct Growth Of Cnt Sponges By Floating Catalyst Cvdmentioning
confidence: 99%
“…In 2007, Yodh's group adopted a solution process to dispersed SWNT powders in water and then converted the suspension to monolithic blocks (aerogels) by freeze-drying. [31][32][33][34][35][36] Although the above solution processes are low-cost and scalable, the inferior mechanical properties in as-prepared CNT aerogels strongly impede their further development and applications. However, the interaction between suspended nanotubes is so weak that the aerogels appear very fragile (easily collapse under compression).…”
mentioning
confidence: 99%
“…Sun et al found that graphene oxide as carbon-based nanomaterials presented the high adsorption capacity for Sr(II) such as 48.72 mg/g at pH 3.0 and T = 298 K [24]. Alternatively, carbon nanofibers (CNFs), as the common carbon-based nanomaterials, have been recently utilized as the highly effective adsorbents in the environmental remediation [25][26][27][28][29]. Liang et al found that CNF-50 (diameter of CNF 50 nm) presented the high adsorption capacity for Pb(II) such as 423.7 mg/g at pH 6.0 [30].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, functional materials with opposite wetting behavior to water and oil liquids are considered to be promising candidates for oil-water separation, due to their high selectivity. The materials selected are including carbon-based three-dimensional (3D) frameworks with porous structures [4][5][6][7][8][9][10][11][12][13], mesh films [14][15][16], and sponges [6,9,13,[17][18][19]. For example, Pan et al fabricated superhydrophobic magnetic foams used for oil removal by pyrolyzing commercial polyurethane sponge grafted with polyelectrolyte layers at 400°C [9].…”
Section: Introductionmentioning
confidence: 98%